A Backward Difference Formulation for Solving Doffing-Van Der Pol Type Oscillators - FadlyNurullahRasedee, Ahmad; Hasan Abdul Sathar, Mohammad; Mohd Ijam, Hazizah; Iskandar Othman, Khairil; Ishak, Norizarina; Raihana Hamzah, Siti; Amalina Jamaludin, Nur (International Journal of Engineering and Technology, 2018)
The study of chaotic motions in periodic self-excited oscillators are an area of interest in science and engineering. The current research proposes a numerical solution in backward difference form for solving these chaotic motions in periodic- self excited oscillators. The research conducted in this study focuses on chaotic motions in the form of Duffing-Van Der Pol Oscillators because of its various applications. A backward difference formulation in predictor-corrector (PeCe) mode is introduced for solving these Duffing-Van Der Pol directly. Numerical simulations provided will show the accuracy of the PeCe backward difference formulation compared against known viable methods. Results will also show that the PeCe backward formulation is a feasible alternative for solving Duffing-Van Der Pol oscillators.Â Â